Answer:
see explanation
Explanation:
(a)
The sum of the 3 angles in a triangle = 180°
Subtract the sum of the given angles from 180° for B
∠ B = 180° - (90 + 63)° = 180° - 153° = 27°
(b)
Using the sine ratio in the right triangle
sin63° =
=
=
( multiply both sides by x )
x × sin63° = 15 ( divide both sides by sin63° )
x =
≈ 16.8 ( to 1 dec. place )
(c)
Using the tangent ratio in the right triangle
tan63° =
=
=
( multiply both sides by y )
y × tan63° = 15 ( divide both sides by tan63° )
y =
≈ 7.6 ( to 1 dec. place )